Validation of Calciphilopteris wallichii and lectotype designation for closely related C. ludens (Cheilanthoideae, Pteridaceae) - Seregin, Alexey P. (Phytotaxa, 2017)
The Moscow University Herbarium holds a nearly complete set of Hugh Cuming’s specimens collected in 1836–1840 in the Philippines (Seregin 2011). Due to a large number of duplicates, Cuming’s specimens played a vital role in the stability of the Malesian plant nomenclature in the 19th century. Bobrov & Gubanov (1979) carefully separated all of the pteridophytes from the Cuming collections at MW and LE and revealed many fern types. Later, Seregin (2011) studied vast collections of flowering plants and cited 420 type specimens of 395 taxa.